Diagnosing dimensions of quality of life at work for general practitioners working in public hospitals - Kherouf, Hayette (Journal of Human Sciences, 2023)
This study aimed to identify the reality of the quality of the work life of general practitioners working in public hospitals across the national territory, a sample of total 72 doctors has been considered. The study is based on the descriptive approach and used the questionnaire as a tool to validate the study.